PENGEMBANGAN CRM TOKO NUC DENGAN BERBASIS WEB - Cosmas Damianus Wijaya; Dedi Trisnawarman; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Nuc is a local business that sells mobile phone accessories, mobile phone and car accessories since october 2015. Customer came from around Indonesia, because Nuc is based on online marketplace. Since increasing business turnover and quantity of items, Nuc needs an independent customer relationship management to ensure customer satisfaction. This application program is a website based. The website contains product information. Customer information, customer complaint information. In collecting data, the author used interview method, While the research method used is the method of SDLC (System Developtment Life Cycle). And in making this application, the author using PHP and MySQL programming language for its database.